The Contribution of Indonesian Islamic Banks to Economic Growth Post-Merger: Opportunities and Challenges - Asriani, Asriani; Kurniawan, Agus; Setyanto, Alief Rakhman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The integration of Islamic finance into Indonesia's national economic strategy is seen as a key driver of sustainable economic growth. However, the Islamic banking sector, despite its potential, continues to face structural and market-related limitations. This study investigates the contribution of Bank Syariah Indonesia (BSI) to Indonesia’s economic growth following the merger of three state-owned Islamic banks Bank Syariah Mandiri, BRI Syariah, and BNI Syariah by focusing on the post-merger opportunities and challenges. The research aims to answer two central questions: (1) What opportunities does BSI hold for contributing to economic development in Indonesia? and (2) What are the major internal and external challenges it must overcome to achieve these goals? Using a qualitative research design, the study gathers primary data through interviews with key informants from BSI branch offices in Aceh, Manado, and West Java, and analyzes secondary data from BSI’s official financial documentation. The results indicate that BSI has consolidated a robust capital base of over Rp239.56 trillion and improved its capacity for financial intermediation, making it a strategic institution aligned with the endogenous growth theory. Nonetheless, BSI’s potential is constrained by issues including underdeveloped governance integration, technological lags, limited regulatory autonomy, and low financial literacy. These findings suggest that while BSI holds strong prospects for supporting inclusive national development, realizing its full potential requires overcoming institutional, technological, and educational gaps. Strengthening legal frameworks, enhancing literacy programs, and harmonizing regulatory policies are essential to maximize BSI’s contribution to Islamic financial and economic advancement in Indonesia.